Screening for depression in Parkinson's disease: the performance of two screening questions. - Baillon, Sarah; Dennis, Michael; Lo, Nelson; Lindesay, James (Age & Ageing, 2014)
Background: the study objective was to evaluate the validity of the two questions recommended by the UK. National Institute for Health and Clinical Excellence for depression screening in Parkinson's disease (PD).Methods: one hundred and twenty patients attending a PD out-patient clinic were interviewed in a standardised manner using relevant sections of the Present State Examination- Schedules for Clinical Assessment in Neuropsychiatry to identify depression according to Diagnostic and Statistical Manual (4th edition) criteria. Participants then completed the two depression screening questions and the 15-item Geriatric Depression Scale (GDS-15).Results: sensitivity, specificity, positive and negative predictive values of the two questions and GDS-15 for major and minor depression combined were calculated for different cut-off scores and a receiver operating characteristics (ROC) analysis was conducted. A threshold of one or more positive responses to the two screening questions gave a sensitivity of 100% and specificity of 84% (positive predictive value 54%, negative predictive value 100%). The area under the ROC curve was 0.95. The optimal cut-off for the GDS-15 was 5/6, which gave a sensitivity of 84% and specificity of 89% (positive predictive value 59%, negative predictive value 97%), and the area under the curve was 0.92.Conclusion: this study shows that the two depression screening questions can be used as an initial screen for depression in patients with PD who have no significant cognitive impairment. A positive response to either of the questions would indicate that further diagnostic assessment may be warranted.